ISLAM DAN KESETARAAN PEREMPUAN DALAM PENDIDIKAN - Ahmad Zumaro (Tarbawiyah Jurnal Ilmiah Pendidikan, 2018)
Education is a human right for every individual and must be given without distinguish of sex. Therefore, education must be reached everyone without distinguish of sexs. But in practice, there are still among the moslems bound the women to get education. This is due to failure in understanding of women obligation to study. The mistaken in understanding text in the Al-Quran or hadith will cause errors in its application and can cause do harm to women